Pelatihan Pemanfaatan Aplikasi Microsoft Excel Dalam Mengolah Absensi Siswa Dan Manajemen Uang Sekolah Di SD Alwasliyah 26 Kp.Bahari - ummi, Khairul Ummi; Adil Setiawan; Soeheri; Rizky Syahputra; Daifiria (Publikasi Pengabdian Masyarakat, 2023)
Training on the Utilization of Microsoft Excel software applications in Processing Student Attendance and Money Management is a spreadsheet processing application program which is one of the most popular computer programs used today. MS Excel has complete facilities and features for data processing purposes. Among the functions that are often used in data processing are: making financial data, making teaching attendance, making student attendance recaps, financial management, processing value data, displaying data with certain criteria, looking for total values ??and to process values, to make criteria values, to convert values, and to make grades according to the 2013 Curriculum easier and more flexible so that they can help teachers at SD Alwasliyah 26 Kp.Bahari school